Prophet of peace: prophet Muhammad for little hearts - Khan, Nafisa; Negi, Pramod (Goodword Books New Delhi, 2008)
Prophet of Peace: Prophet Muhammad for Little Hearts is a beautifully illustrated children's book that introduces young readers to the life and teachings of Prophet Muhammad, highlighting his role as a messenger of peace, compassion, and understanding.